The effect of director-deputy director promotion focus congruence on team knowledge creation: A social identification perspective - Yan, Xue; Liu, Jiakun (Frontiers in Psychology, 2022)
As a new leadership style, promotion focus leadership has attracted the attention of theorists and practitioners. Existing research emphasizes the positive value of director personal promotion focus on team creative behavior while overlooking director-deputy director promotion focus fit. Based on Regulatory Fit Theory and Social Identity Theory, the present study explored the congruence effect of director-deputy director promotion focus on team knowledge creation and the mediating role of team identification. We used polynomial regression and response surface analysis to analyze the data from 674 questionnaires. The results demonstrate that: (1) Director-deputy director congruence in promotion focus is positively related to team identification; (2) Under the condition of director-deputy director promotion focus congruence, the level of team identification does not significantly increase when director-deputy director promotion focus rises from "low-low" to "high-high"; (3) Team identification plays a mediating role in the relationship between director-deputy director promotion focus congruence and team knowledge creation.